Implementation of KH. Hasyim Asy'ari's Educational Thought - Qurotul Aini (Al-Fadlan: Journal of Islamic Education and Teaching, 2023)
KH. Hasyim Asy'ari is a ulama figure, founder of the Tebuireng Islamic boarding school, and founder of NU (Nahdlatul Ulama), the largest religious organization in Indonesia. According to KH. Hasyim Asy'ari, education is very important because with education humans become dignified and noble, and can create a cultured and ethical society. His concept of thinking in education includes the primacy of science and scientists, the primacy of teaching and learning, ethics that must be considered in teaching and learning, namely the ethics of a student towards a teacher, the ethics of students towards lessons and things that must be guided by teachers, the ethics of a teacher, and the ethics of teachers when will teach. According to him, the aim of education for every human being is to become a complete human being in order to get closer to the Creator and obtain happiness in this world and the hereafter. So that a seeker of knowledge manifests his knowledge in daily life with a life of tawakkal, wara', doing good deeds with the hope of Allah's blessing alone, being grateful and etc.